1981
DOI: 10.1029/ja086ia06p04721
|View full text |Cite
|
Sign up to set email alerts
|

Elevated electron temperatures in the auroral E layer measured with the Chatanika Radar

Abstract: An extensive series of spectral measurements has been made in the auroral E region with the Chatanika incoherent scatter radar. Becasue of the small scale length for variations of electron density, temperatures, and ion-neutral collisions we used the operating mode with the best possible range resolution-9 km. About 5% of the time the data exhibited an unusual spectral shape that was most pronounced at 105 and 110 kin. Instead of being almost Gaussian with only a small hint of two peaks, the spectra are much w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Schlegel and St.-Maurice (1981) and Wickwar et al (1981) discovered that, if the electric ®eld strength exceeds about 40 mV/m at high latitudes, the electron temperature around 105±115 km is correlated with the electric ®eld strength (while being generally anti-correlated with electron precipitation at those heights). These basic results were con®rmed by many subsequent studies (see review by for papers prior to 1990; also see Jones et al, 1991;Williams et al, 1992;Haldoupis et al, 1993) and are now accepted as a fact of life in high latitude ionospheric phenomenology.…”
Section: Electronsmentioning
confidence: 99%
“…Schlegel and St.-Maurice (1981) and Wickwar et al (1981) discovered that, if the electric ®eld strength exceeds about 40 mV/m at high latitudes, the electron temperature around 105±115 km is correlated with the electric ®eld strength (while being generally anti-correlated with electron precipitation at those heights). These basic results were con®rmed by many subsequent studies (see review by for papers prior to 1990; also see Jones et al, 1991;Williams et al, 1992;Haldoupis et al, 1993) and are now accepted as a fact of life in high latitude ionospheric phenomenology.…”
Section: Electronsmentioning
confidence: 99%
“…During electron heating events, or in the lower parts of the E-region, these corrections can be substantial (e.g., Sudan, 1995, 1997;Kagan and St.-Maurice, 2004;St.-Maurice and Kissack, 2000;Kissack et al, 1995Kissack et al, , 2008 and we should note that their effects have clearly been observed in the equatorial electrojet (St.-Maurice et al, 2003). An additional problem is that while C S is fairly stable in the equatorial ionosphere, it can vary significantly in the high-latitude region in the presence of electric fields that become so strong that the FB waves themselves will heat the electrons to temperatures well above the ambient atmospheric temperature (e.g., Schlegel and St.-Maurice, 1981;St.-Maurice et al, 1981Wickwar et al, 1981;Jones et al, 1991;Dimant and Milikh, 2003;Milikh and Dimant, 2003;Bahcivan, 2007). Despite extensive data studies on the electron temperature variation with the E × B drift that have been published in the past, the evaluation of C S as a function of the E ×B drift magnitude has rarely been computed as concurrent ion temperatures were usually not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is independent of |E| and levels off at the most probable peak altitude. Interpretation C: levelling-off of h peak at ∼112 km is to be seen in the context of anomalous heating due to FarleyBuneman instability in association with Hall currents which flow preferentially at this altitude (Schlegel and St.-Maurice, 1981;Wickwar et al, 1981). The fact that this feature appears in our statistics shows the high occurrence of this instability (cf.…”
Section: Discussionmentioning
confidence: 76%